Safe asset shortage and collateral reuse - Stephan Jank; Emanuel Mönch; Michael Schneider (Deutsche Bundesbank, 2021)
The reuse of collateral can support the efficient allocation of assets in the financial system. Exploiting a novel dataset, we quantify banks' collateral reuse at the security level. We show that banks substantially increase their reuse of collateral in response to scarcity induced by central bank asset purchases. Repo rates are less sensitive to purchase-induced scarcity at low levels of reuse, when the banking system can easily supply collateral through reuse. Repo rates are more sensitive to scarcity and more volatile at high levels of reuse, highlighting the trade-off between the shock absorption and shock amplification effects of collateral reuse.
Keywords: E4; E5; G1; G2; 330; safe assets; government bonds; collateral reuse; rehypothecation; repo market; securities lending